Benthic foraminifera morphogroups as proxies for paleoecological analysis. An example from the lower cretaceous agua de la mula member of the agrio formation (patagonia, argentina) - Caratelli, Martina (2022)
Fil: Caratelli, Martina. Universidad Nacional de Río Negro, Instituto de Investigación en Paleobiología y Geología. Río Negro; Argentina.